Comparative analysis of global and national systems for observing, monitoring and forecasting natural disasters and hazards with а view to reducing risk - Tuzyak, Yaryna (Technology audit and production reserves, 2021)
The object of research is modern systems for observing, monitoring and forecasting natural disasters and hazards. Although early warning systems are often used to predict the magnitude, location and time of potentially hazardous events, these systems rarely provide impact estimates, such as the expected amount and distribution of material damage, human consequences, service disruption or financial losses. Supplementing early warning systems with predictions of impact has the dual advantage of providing better information to governing bodies for informed emergency decisions and focusing the attention of various branches of science on the goal of mitigating or preventing negative effects. The publication analyses current trends in the growth of natural risks, taking into account the risks associated with global climate change. The issues related to the growing risks of natural disasters and catastrophes at the present stage of societal development and directions of activities at the international and national levels for their reduction are considered. Disaster risk prevention and mitigation measures are described and areas of work in this area are highlighted. The decision-making sequence model is given, global and regional systems of observation, analysis, detection, forecasting, preliminary warning and exchange of information on natural hazards related to weather, climate and water are described. The factors that «unbalance» the global economy in terms of intensity, magnitude, magnitude of losses due to catastrophic events are analyzed. Addressing disaster prevention requires a structure at the national level in each country that includes policy, institutional, legal, strategic and operational frameworks, as well as at the regional and societal levels. This structure will organize and implement disaster risk reduction activities and establish an organizational system that will understand disaster risk and ensure that it is reduced through public participation.